Real-time 3D ultrasound based motion tracking for the treatment of mobile organs with MR-guided high-intensity focused ultrasound. (17th November 2018) - Bour, Pierre; Ozenne, Valéry; Marquet, Fabrice; Denis de Senneville, Baudouin; Dumont, Erik; Quesson, Bruno
Abstract: Introduction: Magnetic resonance-guided high-intensity focused ultrasound (MRgHIFU) treatments of mobile organs require locking the HIFU beam on the targeted tissue to maximise heating efficiency. We propose to use a standalone 3 D ultrasound (US)-based motion correction technique using the HIFU transducer in pulse-echo mode. Validation of the method was performed in vitro and in vivo in the liver of pig under MR-thermometry. Methods: 3 D-motion estimation was implemented using ultrasonic speckle-tracking between consecutive acquisitions. Displacement was estimated along four sub-apertures of the HIFU transducer by computing the normalised cross-correlation of backscattered signals followed by a triangulation algorithm. The HIFU beam was steered accordingly and energy was delivered under real-time MR-thermometry (using the proton resonance frequency shift method with online motion compensation and correction of associated susceptibility artefacts). An MR-navigator echo was used to assess the quality of the US-based motion correction. Results: Displacement estimations from US measurements were in good agreement with 1 D MR-navigator echo readings. In vitro, the maximum temperature increase was improved by 37% as compared to experiments performed without motion correction and temperature distribution remained much more focussed. Similar results were reported in vivo, with an increase of 35% on the maximum temperature using this US-based HIFU target locking. Conclusion: This standalone 3D US-based motion correction technique is robust and allows maintaining the HIFU focal spot in the presence of motion without adding any burden or complexity to MR thermal imaging. In vitro and in vivo results showed about 35% improvement in heating efficiency when focus position was locked on the target using the proposed technique.